The Difference in Level of Depression between Chronic and Non-Chronic Hospitalized Child - Khairunisa, Syarifah Aini; Karini, Suci Murti; Fanani, Mohammad (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2015)
Background: Health problems, either chronic or non-chronic, could possibly cause a depression. Depression in people with health problems often be seen as a normal reaction. In children, most of the time, depression is underdiagnosed or undertreated. This is possibly because children can hardly express their negative thoughts or feels, and they have unspecified somatization. Hence, this study is conducted to find information whether there is any difference in level of depression between chronic and non-chronic hospitalized child. Methods: This is an analytical descriptive study with cross sectional approach using purposive sampling. Data taken from medical records and patients-and-parents interviews using Skala Penilaian Depresi Anak as instrument for measuring the level of depression. The study conducted in 10 weeks, from November 2014 to February 2015. The subjects are 8 to 18 years old Hospitalized Child in RSUD Dr Moewardi Surakarta, as much as 102 patients, consists of 68 chronic patients and 34 non-chronic patients. The data was then analysed using Kolmogorov Smirnov test with a significance value of p < 0.05 in SPSS 20.0 for Windows. Results: The result of Kolmogorov Smirnov test shows the asymptotic significance value of 0.970 (p > 0.05), which means there is no significant difference in level of depression between chronic and non-chronic hospitalized child. Conclusions: There is no significant difference in level of depression between chronic and non-chronic hospitalized child. There should be conducted any further study about depression in hospitalized children including more influential factors that could possibly cause depression. Keywords: Chronic Disease, Non-Chronic Disease, Depression, Hospitalized Child.Â